PRACTICALITY OF FLASHCARD LEARNING MEDIA IN ENVIRONMENTAL POLLUTION MATERIALS FOR CLASS VII SMP/MTs - Tarisyah Taskiya Khalbu; Khalida Ulfa (LPSDI Bina Patria, 2023)
This study discusses the practicality of the flash card learning media for environmental pollution materials for grade 7 SMP/MTs at SMP Negeri 22 Palembang. This study will reveal the level of practicality of the use of learning media by both teachers and students after using learning media in the learning process. The research subjects were carried out with 20 students and 1 teacher. The question sheet has been validated by experts and will be used as an instrument to obtain data as a response from teachers and students regarding the practicality of learning media. The data obtained were processed using a questionnaire analysis technique. The results showed that the flash card learning media had a very practical level of practicality based on the responses of teachers and students. So it can be concluded that the flash card learning media is a very practical learning media to be used in the learning process of environmental pollution by teachers and students.